Oplan Balikbayan [videorecording] - Lazaro, Cheche; Ramos, Angie (Quezon City Probe Productions, 1993)
An investigative report on the Ninoy Aquino assassination specifically the military task force assigned to handle the security matters on the day of his return to the Philippines.
VHS.
Keywords: Aquino, Benigno, 1932-1983 -- Assassination; Philippines -- History -- 1986.